Antibiofilm activity and NMR-based metabolomic characterization of cell-free supernatant of Limosilactobacillus reuteri DSM 17938 - Vitale, Irene; Spano, Mattia; Puca, Valentina; Carradori, Simone; Cesa, Stefania; Marinacci, Beatrice; Sisto, Francesca; Roos, Stefan; Grompone, Gianfranco; Grande, Rossella (Frontiers in Microbiology, 2023)
The microbial biofilm has been defined as a “key virulence factor” for a multitude of microorganisms associated with chronic infections. Its multifactorial nature and variability, as well as an increase in antimicrobial resistance, suggest the need to identify new compounds as alternatives to the commonly used antimicrobials. The aim of this study was to assess the antibiofilm activity of cell-free supernatant (CFS) and its sub-fractions (SurE 10 K with a molecular weight <10 kDa and SurE with a molecular weight <30 kDa), produced by Limosilactobacillus reuteri DSM 17938, vs. biofilm-producing bacterial species. The minimum inhibitory biofilm concentration (MBIC) and the minimum biofilm eradication concentration (MBEC) were determined via three different methods and an NMR metabolomic analysis of CFS and SurE 10K was performed to identify and quantify several compounds. Finally, the storage stability of these postbiotics was evaluated by a colorimetric assay by analyzing changes in the CIEL*a*b parameters. The CFS showed a promising antibiofilm activity against the biofilm developed by clinically relevant microorganisms. The NMR of CFS and SurE 10K identifies and quantifies several compounds, mainly organic acids and amino acids, with lactate being the most abundant metabolite in all the analyzed samples. The CFS and SurE 10 K were characterized by a similar qualitative profile, with the exception of formate and glycine detected only in the CFS. Finally, the CIEL*a*b parameters assess the better conditions to analyze and use these matrices for the correct preservation of bioactive compounds.